Comparative Analysis of Financial Performance of Sharia Banks from Indonesia and the United Kingdom - Sukmawati, Cindy Putri (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The rapid progress of Islamic banking development is evident in the increasing pace of Sharia banking. The financial performance of individual banks serves as a key indicator of Islamic banking growth. Islamic banking exhibits distinctive characteristics and advantages from various perspectives. This research aims to discern variations in the financial performance of two countries, namely Indonesia and the United Kingdom. The study focuses on Islamic banking entities in both countries, with Bank Syariah Indonesia (BSI), Bank Muamalat Indonesia (BMI), Bank Tabungan Pensiunan Nasional Syariah (BTPN), Abu Dhabi Islamic Bank (ADIB), Bank of London & The Middle East (BLME), and Al Rayan Bank UK (ARB) selected as research samples. The CAMEL method is employed as the performance measurement approach in this study. A quantitative approach is adopted, utilizing descriptive statistical analysis through the SPSS test tool. The findings of the descriptive statistical analysis reveal significant discrepancies in CAR, NPF, NPM, ROA, and FDR ratios among Islamic banks in Indonesia and the United Kingdom. The implications of this research are anticipated to serve as a basis for introspection and foster enhancements in the performance of each Islamic bank.